Pembangunan Manusia: Filosofi dan Praksis Pembangunan yang Bermartabat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Abstract Indonesia has infrastructure constrains,such as the need for food, health, and nutrition and the spreading of disease. In return, this conditon has caused low life quality of Indonesian people compared to other Asean countries. The richness in competing with other countries. The gap between the rich and poor, East and West, rural and urban, local people and outsider, gender imbalance became another contraints in building human capital in Indonesia.